2021
DOI: 10.1097/dcc.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation, and Impact of a Proning Team During the COVID-19 Intensive Care Unit Surge

Abstract: Background: Prone positioning has been used as an intervention to improve oxygenation in critically ill patients with acute respiratory distress syndrome. During the COVID-19 pandemic, resources were even more limited given a surge in acute respiratory distress syndrome patients, which outstripped intensive care unit (ICU) capacity at many institutions.Local Problem: The purpose of this article is to describe the development and implementation of a proning team during the surge in ICU patients with COVID-19 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Small, observational studies published early in the pandemic 59 , 60 , 61 , 62 showed improved oxygenation through prone positioning, and further observational data described reduced mortality in those patients on mechanical ventilation who were proned 63 , 64 , 65 . Proning protocols were developed, and some centers created specific proning teams to provide relief for the core intensive care team 66 , 67 , 68 . Intermittent prone positioning became standard of care for intubated patients with ARDS secondary to COVID-19, mainly based on literature showing reduction in mortality in non-COVID ARDS 54 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Small, observational studies published early in the pandemic 59 , 60 , 61 , 62 showed improved oxygenation through prone positioning, and further observational data described reduced mortality in those patients on mechanical ventilation who were proned 63 , 64 , 65 . Proning protocols were developed, and some centers created specific proning teams to provide relief for the core intensive care team 66 , 67 , 68 . Intermittent prone positioning became standard of care for intubated patients with ARDS secondary to COVID-19, mainly based on literature showing reduction in mortality in non-COVID ARDS 54 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Issues identified included unsafe staffing ratios, lack of education or resources to safely prone patients, and knowledge deficits related to sedation and neuromuscular blockade utilization. Recognition of these gaps in care and subsequent use of the data to drive process improvement initiatives, such as implementing PPV turning teams and providing opportunities for education and simulation, required the use of a learning system to inform patient safety efforts 10 …”
Section: Discussionmentioning
confidence: 99%
“…Many departments sought to create specific teams to undertake procedures such as proning, line insertions and intubation, thus allowing specific professional skills to be channelled to the area's most in need. 18 , 19 , 20 , 25 , 51 , 53 Open communication within teams along with a clear understanding of the common goal, exemplified teamworking at its best. 52 The nature of the ITU environment demands transparent communication between all members of the interprofessional team.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies recognised the need for dedicated proning teams and a proning champion. 18 , 19 , 20 In many cases, staff redeployed into ITU during the pandemic were predominantly involved in the practice of proning patients. 18 , 19 , 21 …”
Section: Introductionmentioning
confidence: 99%